Knowledge Level of Dairy Farmers About Brucellosis in Punjab - Khurana, Naman; Kasrija, Rajesh; Sharma, Rajnish; Sharma, Rakesh Kumar (The Indian Journal of Animal Reproduction, 2025)
Brucellosis is an important zoonotic disease across the world; it not only has impact on human and animal health but also on economy of the farm families in particular and of nation in general. Brucellosis has been reported in livestock in several states of our country including Punjab. The present study was conducted in all the agro-climatic zones of Punjab state. A total of 394 dairy farmers (holding minimum of 5 milch animals) were selected randomly and the information was gathered by personal interview schedule. Most of the respondents from all the six zones were above 30 years of age. In overall Punjab, only 3.0 percent dairy farmers were illiterate, while others have education level above high school. There was a statistically significant difference in knowledge score between different agro-climatic zones (H=11.687, df=5, p0.05) and between farm size (H=0.670, df=2, p>0.05). From the present study, it is concluded that, there is dire need to organize suitable knowledge enrichment drive about brucellosis in the state.
Keywords: Brucellosis; Dairy; Knowledge; Punjab; Zoonoses